Potential of Tyrophagus putrescentiae (Schrank) (Astigmata: Acaridae) for the Biological Control of Lasioderma serricorne (F.) (Coleoptera: Anobiidae) - Glauco da Cruz Canevari (Brazilian Archives of Biology and Technology, 2012)
This work investigated the potential of Tyrophagus putrescentiae (Schrank) (Astigmata: Acaridae) to control Lasioderma serricorne (F.) (Coleoptera: Anobiidae) in the laboratory. L. serricorne is the most destructive insect pest ever found on stored tobacco. The experimental delineation had 33 arenas being each experimental unit with 11 arenas of experiments with eggs, larva of L. serricorne with the density of T. putrescentiae maintained constant, where from 11 of these arenas, eight were for the analysis of predation and three to evaluate the natural mortality of the insect. The highest predation rate was found during the larval stage with, approximately, 54, 68 and 78% mortality of L. serricorne from the fourth until the sixty day of predation. These results indicated that it was possible to use the predatory mite T. putrescentiae in pest management programs of L. serricorne in the storage units of tobacco.